Porous copper oxide catalyst and application thereof

By using porous copper oxide catalyst, the problem that hydrogen evolution reaction under acidic conditions in the prior art is better than eCO2RR, and an efficient electrochemical carbon dioxide reduction reaction in alkaline flow electrolytic cells is achieved, which significantly improves the reaction efficiency and product selectivity.

CN119503859APending Publication Date: 2025-02-25INST OF NEW MATERIALS & IND TECH WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424380.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing electrochemical carbon dioxide reduction reaction (eCO2RR) catalysts have kinetic favorable hydrogen evolution reaction (HER) under acidic conditions, which is better than eCO2RR, resulting in insufficient reaction efficiency and product selectivity.

Method used

Porous copper oxide catalyst is used, which is prepared by mixing copper nitrate, glycine, ethylene glycol and water and heating at 200-800°C. It has a porous structure and is suitable for electrocatalytic reactions and electrochemical reduction carbon dioxide reactions.

Benefits of technology

In the alkaline flow electrolytic cell, the porous copper oxide catalyst exhibits excellent electrocatalytic activity and good catalytic stability, achieving 50.5% C2H4 Faraday efficiency and over 60% C2+ product Faraday efficiency, significantly improving the reaction efficiency and product selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503859A_ABST
    Figure CN119503859A_ABST
Patent Text Reader

Abstract

The invention provides a porous CuO catalyst and application thereof.The porous CuO catalyst is prepared by adding cupric nitrate, glycine and ethylene glycol into deionized water, fully and uniformly mixing, then putting the mixture into a porcelain boat, and heating the mixture at a high temperature in a muffle furnace. The catalyst is loaded on a substrate gas diffusion layer (GDL) and can be used for electrocatalytic reduction of carbon dioxide (eCO2RR). In an alkaline flow electrolytic tank, the catalyst shows excellent electrocatalytic activity and good catalytic stability. When the current density is 200mA cm <-2 >, the Faraday efficiency of the catalyst to C2H4 reaches 50.5%, and meanwhile, the Faraday efficiency of a C2 + product also exceeds 60%. The unique porous structure is more beneficial to bubble management in a flowing electrolytic tank, stabilizes a solid-liquid-gas three-phase interface, and has more excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical reduction of carbon dioxide, and in particular relates to a porous copper oxide catalyst and application thereof. Background Art

[0002] With the continuous development of social technology, air pollution has become a key issue affecting people's lives. Carbon dioxide in the atmosphere is the culprit of the greenhouse effect. Efficiently and selectively converting greenhouse gases (such as carbon dioxide) that affect the environment into usable chemicals is one of the most critical issues facing current carbon dioxide conversion research. As an emerging technology, the electrochemical carbon dioxide reduction reaction (eCO2RR) has attracted widespread attention due to its mild operating conditions, adjustable products, and easy coupling with renewable energy. With the development of photovoltaic and wind power generation, cheaper electricity prices have made electrochemically driven catalytic reactions economically feasible.

[0003] When evaluating the performance of the catalyst eCO2RR, the influence of the electrolyzer is also huge. At present, the laboratory often uses H-type electrolyzers and flow electrolyzers to evaluate the performance of eCO2RR. The most significant difference between the flow cell and the H-type cell is the GDL structure. In the flow cell, one side of it is exposed to CO2 and the other side is exposed to the electrolyte, thereby allowing the coexistence of the gas phase, liquid phase and solid phase three-phase interface, greatly improving mass transfer. The current density of the flow electrolyzer has also been significantly improved to the ampere level.

[0004] In a flow electrolyzer, the choice of electrolyte is also a very critical link. Carrying out eCO2RR in an acidic electrolyte has many advantages such as high carbon efficiency and energy efficiency. However, under acidic conditions, the kinetically favorable hydrogen evolution reaction (HER) is superior to eCO2RR. The use of alkaline solutions can greatly limit the HER reaction and further improve the reaction efficiency. The improvement of CO2 mass transfer significantly accelerates the reaction kinetics of eCO2RR and optimizes product selectivity.

[0005] Copper-based electrocatalysts can produce multi-carbon products with high energy density and wide applicability. There are four ways to adjust the selectivity and efficiency of copper-based catalysts, including designing tandem catalysts, adjusting the electronic structure of catalysts, exposing the selective facets of catalysts, and using additives. Tandem catalysts adjust the reaction selectivity of target products by introducing another non-copper-based metal catalyst with different binding abilities to reaction intermediates. Different copper crystal faces have different binding abilities to C 2+ The products have different selectivities, and selectively exposing certain crystal faces of copper can improve the selectivity of certain target products. We choose to expose the selective faces of the catalyst to allow the copper-based catalyst to have more contact with the reactants and to effectively manage water. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a porous copper oxide catalyst and its application.

[0007] The technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention provides a porous copper oxide catalyst, characterized in that it is a copper oxide catalyst with a porous structure obtained by mixing copper nitrate, glycine, ethylene glycol and water and heating at 200-800°C.

[0009] Preferably, it is a copper oxide catalyst with a porous structure obtained by mixing copper nitrate, glycine, ethylene glycol and water and heating at 300-500°C.

[0010] Preferably, the molar ratio of copper nitrate to glycine is 2-12:1.

[0011] Preferably, the molar ratio of copper nitrate to glycine is 6-8:1.

[0012] Preferably, the volume ratio of ethylene glycol to water is 1:0.5-150.

[0013] Preferably, the volume ratio of ethylene glycol to water is 1:0.5-1.

[0014] A second aspect of the present invention provides a porous copper oxide catalyst as described above for use in an electrocatalytic reaction.

[0015] The third aspect of the present invention provides a porous copper oxide catalyst as described above for use in an electrochemical reduction of carbon dioxide reaction.

[0016] Preferably, the gas diffusion electrode is used as the cathode of the flow electrolysis cell.

[0017] The method for preparing the gas diffusion electrode comprises the following steps:

[0018] (1) dispersing a porous copper oxide catalyst into a mixed solution containing n-PrOH, Nafion, THF and CNTs to prepare a catalyst slurry;

[0019] (2) Coat the catalyst slurry on the gas diffusion layer.

[0020] The beneficial effects of the present invention are as follows:

[0021] The present invention adds copper nitrate, glycine and ethylene glycol to deionized water, mixes them thoroughly, and then puts them into a porcelain boat and heats them at high temperature in a muffle furnace to successfully prepare porous CuO. The catalyst is loaded on a substrate gas diffusion layer (GDL) and can be used for electrocatalytic reduction of carbon dioxide (eCO2RR). In an alkaline flow electrolytic cell, the catalyst exhibits excellent electrocatalytic activity and good catalytic stability. When the current density is 200 mA cm -2 When the catalyst has a Faradaic efficiency of 50.5% for C2H4, 2+ The Faraday efficiency of the product is also over 60%. The unique porous structure is more conducive to bubble management in the flow electrolytic cell, stabilizes the solid-liquid-gas three-phase interface, and has better catalytic performance.

[0022] The porous structure can effectively manage water and improve the stability of the solid-liquid-gas three-phase interface. Secondly, the catalyst has a larger surface area, which increases the number of active sites and improves the selectivity of the Cu-based catalyst for ethylene. This work provides a powerful way to efficiently convert CO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0024] Figure 1 This is a scanning electron microscope (SEM) image of the porous CuO prepared in Example 1;

[0025] Figure 2 The eCO2RR performance of the porous CuO prepared in Example 1 in a flow electrolytic cell with 1M KOH as the cathode electrolyte;

[0026] Figure 3 The eCO2RR stability performance test of the porous CuO prepared in Example 1 in a flow electrolytic cell with 1M KOH as the cathode electrolyte;

[0027] Figure 4 CV diagram of porous CuO prepared in Example 1

[0028] Figure 5 The porous CuO prepared in Example 1 was -2 The samples were pre-reduced for 30 min and X-ray diffraction (XRD) test was performed.

[0029] Figure 6The porous CuO prepared in Example 1 was -2 Pre-reduction for 30 min, X-ray photoelectron spectroscopy (XPS) test

[0030] Figure 7 Performance comparison of porous CuO, CuO-200℃ and porous CuO-800℃ prepared in Example 1, Example 9 and Comparative Example 1

[0031] Figure 8 For CuO-200℃ at 50mA cm -2 Pre-reduction for 30 min, scanning electron microscope (SEM) image.

[0032] Fig. 9 For porous CuO-800℃ at 50mA cm -2 Pre-reduction for 30 min, scanning electron microscope (SEM) image. DETAILED DESCRIPTION

[0033] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0034] Example 1

[0035] 815 mg Cu(NO3)2·3H2O, 35.25 mg glycine, and 7.5 ml ethylene glycol were dissolved in 7.5 ml deionized water, stirred evenly for 30 min, and then transferred to a porcelain boat, placed in a muffle furnace preheated to 400°C, and reacted at high temperature for 30 min. After the reaction was completed, the porcelain boat was taken out and cooled to room temperature to obtain a black porous CuO solid powder.

[0036] Application Example 1

[0037] The porous CuO powder obtained in Example 1 was dispersed into a mixed solution containing n-PrOH, THF and CNTs, and then physically mixed with Nafion. The mixture was then ultrasonicated for 30-60 minutes to prepare a porous CuO catalyst slurry. The solution was evenly dripped on a 1×2 cm 2 The loading amount was 0.5 mg cm -2 , prepare gas diffusion electrode.

[0038] Example 2

[0039] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 70.5 mg glycine, and 0.1 ml ethylene glycol are dissolved in 15 ml deionized water. The final product is named porous CuO1 / 8 .

[0040] Example 3

[0041] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 35.25 mg glycine, and 0.1 ml ethylene glycol are dissolved in 15 ml deionized water. The final product is named porous CuO 1 / 4 .

[0042] Example 4

[0043] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 141 mg glycine, and 0.1 ml ethylene glycol are dissolved in 15 ml deionized water. The final product is named porous CuO1.

[0044] Example 5

[0045] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 35.25 mg glycine, and 0.5 ml ethylene glycol are dissolved in 15 ml deionized water. The final product is named porous CuO-1.

[0046] Example 6

[0047] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 35.25 mg glycine and 1 ml ethylene glycol are dissolved in 14 ml deionized water. The final product is named porous CuO-2.

[0048] Example 7

[0049] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 35.25 mg glycine, and 5 ml ethylene glycol are dissolved in 10 ml deionized water. The final product is named porous CuO-3.

[0050] Example 8

[0051] The difference between this embodiment and embodiment 1 is that 815 mg Cu(NO3)2·3H2O, 35.25 mg glycine, and 10 ml ethylene glycol are dissolved in 5 ml deionized water. The final product is named porous CuO-5.

[0052] Example 9

[0053] The difference between this embodiment and embodiment 1 is that the ceramic boat is placed in a muffle furnace preheated to 200°C for high temperature reaction for 3 hours. After the reaction is completed, the ceramic boat is taken out and cooled to room temperature to obtain a black porous CuO solid powder, named CuO-200°C.

[0054] Example 10

[0055] The difference between this embodiment and embodiment 1 is that the ceramic boat is placed in a muffle furnace preheated to 600°C for high temperature reaction for 30 minutes. After the reaction is completed, the ceramic boat is taken out and cooled to room temperature to obtain a black porous CuO solid powder, named CuO-600°C.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 1 is that the ceramic boat is placed in a muffle furnace preheated to 800°C for high temperature reaction for 30 minutes. After the reaction is completed, the ceramic boat is taken out and cooled to room temperature to obtain a black porous CuO solid powder, named CuO-800°C.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 1 is that 815 mg Cu(NO3)2·3H2O and 0.1 ml ethylene glycol are dissolved in 15 ml deionized water. The final product is named porous CuO0.

[0060] The electrical performance of the gas diffusion electrode prepared according to Example 1 was tested. The electrolytes at both the cathode and cathode were 1 M KOH, the CO2 flow rate in the gas chamber was controlled at 15 sccm, and the current density was 50 mA cm -2 The three-electrode flow electrolytic cell was pre-reduced for 30 min, and the SEM images were shown in Figure 2. Figure 1 shown.

[0061] The eCO2RR performance test was carried out under the same conditions, such as Figure 2 The catalyst prepared in Example 1 can achieve a maximum of 400 mA cm -2 The current density is 200 mA cm -2 At a current density of 1.5 mol / L, the selectivity for ethylene reached a maximum of 50.5%. The catalyst was then tested for stability. Figure 3 As shown, at 200mA cm -2 At a current density of 1.5 Å, the catalyst performance can be stable for at least 220 min, and the selectivity to ethylene remains above 45%. After 230 min, the performance begins to decline, the voltage increases, and the selectivity to ethylene is less than 35%.

[0062] The catalyst was tested by cyclic voltammetry (CV). Figure 4shown.

[0063] The catalyst was -2 The electrolyte on the GDL was washed off with deionized water, and the deionized water was dried with nitrogen. X-ray diffraction (XRD) test was performed. Figure 5 shown.

[0064] The catalyst was -2 After pre-reduction for 30 min, the electrolyte on the GDL was washed off with deionized water, and the deionized water was blown dry with nitrogen. X-ray photoelectron spectroscopy (XPS) test was performed. Figure 6 shown.

[0065] At 200mA cm -2 The two catalysts prepared in Example 9 and Comparative Example 1 were made into electrodes in the same manner as in Application Example 1 at a current density of , and then performance tests were performed. Figure 7 As shown, CuO-200℃ and porous CuO-800℃, at 200mAcm -2 The selectivities to ethylene at current densities of 50.5% and 18% respectively, which are much lower than those in Example 1.

[0066] The catalysts prepared in the examples and comparative examples were made into gas diffusion electrodes using the preparation method of Application Example 1. -2 The Faraday efficiency of ethylene was tested under 37 °C. The results are shown in Table 1.

[0067] Table 1. Electrochemical efficiency of catalysts prepared at different glycine, ethylene glycol and deionized water dosages and temperatures

[0068]

[0069] Comparative Example 2 and Examples 2-4 show that with the increase of glycine, the selectivity of the catalyst for ethylene is distributed in a volcano-like manner. 1 / 4 The performance is optimal.

[0070] Secondly, in Examples 1, 5-8, the ratio of ethylene glycol to water was adjusted based on the fixed amount of glycine. As shown in Table 1 above, when the amount of water and ethylene glycol were both 7.5 ml, at 200 mA cm -2 The selectivity of porous CuO for ethylene is as high as 50.5%.

[0071] Finally, Examples 9-10 and Comparative Example 1 obtained CuO-200°C, CuO-600°C, and CuO-800°C by adjusting the temperature on the basis of a fixed reaction raw material ratio (Note: CuO-200°C was in a muffle furnace for 3 hours). The selectivity for ethylene was the highest at 200°C, which was 50.5%, the same as the porous CuO obtained in Example 1, but CuO-200°C could not achieve a high current density, and its stability was not as good as that of the porous CuO in Example 1. The porous CuO in Example 1 was the best sample.

[0072] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A porous copper oxide catalyst, characterized in that The invention is a copper oxide catalyst with a porous structure obtained by mixing copper nitrate, glycine, ethylene glycol and water and heating the mixture at 200-800°C.

2. A porous copper oxide catalyst according to claim 1, characterized in that: The invention is a copper oxide catalyst with a porous structure obtained by mixing copper nitrate, glycine, ethylene glycol and water and heating the mixture at 300-500°C.

3. A porous copper oxide catalyst according to claim 1, characterized in that: The molar ratio of the copper nitrate to glycine is 2-12:

1.

4. A porous copper oxide catalyst according to claim 1, characterized in that: The molar ratio of the copper nitrate to glycine is 6-8:

1.

5. A porous copper oxide catalyst according to claim 1, characterized in that: The volume ratio of the ethylene glycol to water is 1:0.5-150.

6. A porous copper oxide catalyst according to claim 1, characterized in that: The volume ratio of the ethylene glycol to water is 1:0.5-1.

7. A porous copper oxide catalyst as described in any one of claims 1 to 6 is used in an electrocatalytic reaction.

8. A porous copper oxide catalyst as described in any one of claims 1 to 6 is used in an electrochemical reduction of carbon dioxide reaction.

9. The use according to claim 8, characterized in that: It uses a gas diffusion electrode as the cathode of the flow electrolytic cell. The method for preparing the gas diffusion electrode comprises the following steps: (1) dispersing a porous copper oxide catalyst into a mixed solution containing n-PrOH, Nafion, THF and CNTs to prepare a catalyst slurry; (2) Coat the catalyst slurry on the gas diffusion layer.